The relative influence of coaches, parents, and peers on college athletes` self -determined motivation and perceived effort in sport - Zhang, T.; Xiang, X.; Gu, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The influence of coaches, parents, and peers structure on an athletes achievement and motivation is recognised. However, there is limited research which has evaluated the nature and extent of these influences. The purpose of this study therefore, was to examine the task- and ego-involving roles of these other influences in predicting different levels of self-determined motivation and perceived effort in college athletes. Methods Participants were 164 college athletes (mean age 21.13 years) enrolled in various competitive sports including volleyball, basketball, and soccer from an eastern city in China. They completed the Significant Others` Goal-Involving Roles in Sport Questionnaire (SOGIRSQ; Bars et al., 2006), the Situational Motivation Scale (SIMS; Guay et al., 2000), and the perceived effort (McAuley, Duncan, & Tammen, 1989) measure during their last week of training. Data were analyzed using Pearson correlations to examine the complex relationships among these variables. A serious of multiple regression analyses were performed to assess the relative contributions of these factors on the selfdetermined motivation, perceived effort, and the predictive utility of coaches, parents, and peers toward different levels of self-determined motivation. Results Correlation analyses revealed a pattern of positive correlations among the significant others` take- and ego-involving behaviours, self-determined motivation, and perceived effort (r`s ranging from .18 to .70). Multiple regression analyses further revealed that important predictors of perceived effort ( 2 = 53.5 %) were Promotion of learning by coaches PLC ( = .46, p< .01), Pursuit of learning by athletes, PLA ( = .17, p< .05), IM ( = .35, p< .01), and Athlete motivation, AM ( = -.22, p< .01). For Intrinsic motivation IM, PLA ( = .32, p< .01), promotion comparison by parents, PCP ( = .22, p< .01), and PLC ( = .21, p< .05) emerged as positive predictors ( 2 = 37.9 %). For identified regulation,IR, PLA ( = .26, p< .01), PCA ( = .26, p< .01), and PLC ( = .20, p< .05) emerged as positive predictors ( 2 = 35.3 %). For ER or low levels of motivation, PLA ( = .25, p< .01) and PCA ( = .41, p< .01) were two positive predictors ( 2 = 32.2 %). For AM, PCA ( = .52, p< .01) emerged as the only positive predictor ( 2 = 26.5 %). Discussion / Conclusions The findings of the present study indicated that perceived tasks involving behaviours of coaches and peers, and high levels of self-determined motivation had an impact on students` perceived effort. Further, the results also highlight the important influence of perceived task-involving behaviours of coaches and peers on high levels of self-determined motivation, and perceived ego-involving behaviours of peers on low levels of self-determined motivation. These suggest that increasing coaches and peers task-involving behaviours or decreasing their ego-involving behaviours can be effective in promoting college athletes` motivation and engagement in competitive sports. Therefore, emphasizing task mastery, personal improvement, and learning is significant in competitive sports.